The Legacy of Roman Law in the German Romantic Era : Historical Vision and Legal Change. - Whitman, James Q., 1957- (Princeton legacy library., 2014)
Well after the process of codification had begun elsewhere in nineteenth-century Europe, ancient Roman law remained in use in Germany, expounded by brilliant scholars and applied in both urban and rural courts. The survival of this flourishing Roman legal culture into the industrial era is a familiar fact, but until now little effort has been made to explain it outside the province of specialized legal history. James Whitman seeks to remedy this neglect by exploring the broad political and cultural significance of German Roman law, emphasizing the hope on the part of German Roman lawyers th.